Analisis Peran dan Dampak Zakat Digital Sebagai Upaya Pengentasan Kemiskinan di Jakarta - Nur Khayin Muhdlor (Universitas Syiah Kuala, 2023)
Poverty is a serious problem in the Jakarta area that has significant social and economic impacts. In order to overcome this problem, digital zakat emerged as an innovation in the collection, distribution, and management of zakat using digital technology. The purpose of this study is to analyze the role and impact of digital zakat as an effort to alleviate poverty in the Jakarta area. This research uses a qualitative method. The data collection technique is done by literature study. The data that has been collected is then analyzed through the process of coding and categorization. The results showed that digital zakat plays a role in increasing public access to zakat, so that it can improve the welfare of the poor. While the impact of digital zakat on poverty alleviation in the Jakarta area can be seen from several aspects, namely in the economic aspect, digital zakat can help increase the income of the poor, so as to improve their welfare. While the social aspect, digital zakat can help improve the access of the poor to education, health, and food. While the spiritual aspect, digital zakat can help increase the faith and piety of the poor.